Deodorant cap lodged in the rectum: A case report - Reddy, Tavishala Amarasimha; Verma, Ankur; Haldar, Meghna; Jaiswal, Sanjay; Sheikh, Wasil Rasool; Vishen, Amit; Snehy, Abhishek; Ahuja, Rinkey (Indian Journal of Case Reports, 2019)
Anorectal foreign bodies are rare but have shown a rising trend in recent times. Various kinds of a foreign object may be observed in the rectum, including sharp instruments which may pierce rectum, colon, or create visceral organ injuries. Most common presenting symptoms include abdominal, rectal pains and bleeding per rectum. Without proper history and examination, these foreign objects can easily be missed in the emergency department as these are still a matter of taboo especially in countries like India. We report a case of anelderly gentleman who presented to the emergency with bleeding per rectum and did not initially give a history of foreign body insertion.